Antibacterial and antispasmodic activities of a dichloromethane fraction of an ethanol extract of stem bark of Piliostigma reticulatum - N'Guessan, B.B.; Dosso, K.; Gnangoran, B.N.; Amoateng, P.; Asiedu-Gyekye, I.J.; Yapo, A.P. (Journal of Pharmacy & Bioallied Sciences, 2015)
This study presents the antispasmodic and antibacterial properties of an ethanol extract and fractions the of stem bark of Piliostigma reticulatum. The antispasmodic effects of the extract and its fractions were performed on isolated rabbit duodenum. The antibacterial properties were determined as minimal inhibitory and bactericidal concentration of the extract and fractions of P. reticulatum on susceptible and resistant strains of Escherichia coli, Vibrio cholerae, Staphylococcus aureus, Shigella dysenteriae and Salmonella tiphymurium. The ethanol extract of P. reticulatum and fractions (except for heptane) produced concentration-dependent relaxant effects on isolated duodenum preparations. The IC50 of the extract and dichloromethane, ethyl acetate, butanol and aqueous fractions are 0.88452, 0.2453, 0.2909, 0.3946 and 0.3231 mg/ml respectively. The extract was found to significantly antagonize acetylcholine-induced contraction. The susceptible strains E. coli and V. cholerae were the most inhibited by the dichloromethane fraction at 60 mg/mL, as shown by their diameter of inhibition of 13.2 ± 0.76 and 13.3 ± 0.67 mm respectively. Conversely, the dichloromethane fraction, the most active antibacterial fraction, did not inhibit the resistant strains S. dysenteriae and S. tiphymurium. The results showed that P. reticulatum stem bark possesses spasmolytic and antibacterial properties and this may contribute to its traditional medicinal use for the treatment of diarrhea. (PDF) Antibacterial and antispasmodic activities of a dichloromethane fraction of an ethanol extract of stem bark of Piliostigma reticulatum. Available from: https://www.researchgate.net/publication/274698348_Antibacterial_and_antispasmodic_activities_of_a_dichloromethane_fraction_of_an_ethanol_extract_of_stem_bark_of_Piliostigma_reticulatum [accessed Oct 31 2018].
Keywords: Antibacterial; diarrhea; Piliostigma reticulatum; spasmolytic effects